Penetration performance of double-ogive-nose projectiles. (October 2015) - Liu, Jiancheng; Pi, Aiguo; Huang, Fenglei
Abstract: The penetration ability of projectiles is closely related to their nose shape as this influences the high-velocity or ultrahigh-velocity kinetic-energy penetration of a rigid projectile. Based on classical cavity expansion theory and a double-ogive-nose scheme, this study set out to analyze the dependency relationship between the nose shape factor N ∗ and the double-ogive characteristic parameters. This paper first discusses the effects of different nose shapes on the penetration performance of a projectile. The paper then proposes a double-ogive-nose penetration body scheme with a low penetration resistance. A penetration experiment with the double-ogive-nose projectile is set up and a Holmquist–Johnson–Cook concrete [1] model is described, together with its application to the prediction of the tendency of the depth of penetration. A comparison between the results of the experiment, simulation, and calculation for the ogive nose and double-ogive-nose projectiles proves that the analysis and the proposed method are both reasonable and feasible. Highlights: A double-ogive-nose penetration body scheme with a low penetration resistance is proposed. The influence of the nose shape coefficient N ∗ on the penetration resistance and DOP is discussed. The feasibility of the proposed method is validated through theoretical, experimental, and simulation results.